Influences on engineering enrolments. A synthesis of the findings of recent reports - Prieto, Elena; Holbrook, Allyson; Bourke, Sid; O'Connor, John; Page, Adrian; Husher, Kira (European journal of engineering education, 2009)
The decline in engineering degree enrolments in many western nations poses a range of challenges that are easy to identify but difficult to address. There have been at least 30 major reports on the issue of engineering enrolments in universities and a great many more on an allied issue, enrolments and achievement in science and maths areas at a secondary school level. Typically such reports are funded through government or private agencies at local, regional and national level, and their authors obtain access to significant numbers of respondents, and secondary data sources; however, because of their size and scope the reports are rarely synthesised. Indeed, their lack of influence is often noted and deplored. This study undertakes the task of drawing together reports directed specifically at engineering enrolments to identify the main influences that result in enrolments or work against enrolments. The influences identified fall into four strands and can be seen to form the basis of a complex structure; understanding of the structure has the potential to enhance future research in this critically important area.